Why Did Southeast Asia’s Military Expenditure Increase During a Recession? - Sugiarto Pramono; Claudia Syarifah; Sujit Kumar Datta (JURNAL ILMU SOSIAL, 2023)
The world is in recession, Covid-19 and the Ukraine Crisis are two important events that have made the world economy worse. The World Bank predicts an increased risk of a global recession in 2023. A recession will impact many aspects of life, including the military. This is reasonable because efforts to overcome them are prioritized in the main sectors. Something is fascinating about Southeast Asia, namely that its military expenditure has increased. Why did Southeast Asia's military expenditure increase during a recession? This pattern of contradic- tion is not only important but also interesting to study. Using qualitative methods with data analysis techniques, and borrowing a structural realism approach, it is found that the in- creasing competition between the U.S.A. and China has triggered an increase in military ex- penditure in the region. At the same time conflicts and potential conflicts between countries in the Southeast Asian region, although not directly, are permanent causes. The recession does not seem to affect efficiency in military expenditure, this shows that tensions in Southeast Asia are a priority of countries in the region. These findings close a gap in previous studies which were relatively dominated by efforts to link military expenditure to economic growth using quantitative methods